Pemberdayaan Kelompok Tani Melalui Pembuatan Pupuk Organik di Tammerodo Sendana Majene - Mutthalib (Jurnal Berita Sosial, 2022)
Empowerment of farmer groups through the manufacture of organic fertilizer is part of the strategy for strengthening the capacity of farmer groups through the manufacture of organic fertilizers. This type of research is a qualitative research using a phenomenological approach. Sources of data in this study are primary data sources obtained based on interviews with relevant parties in the field and secondary data, namely data sources collected from relevant books and documents. Data collection methods used are observation, interviews and documentation. Then the data analysis was carried out through five stages, namely: Making a list of expressions (bracketing), reduction and elimination, creating clusters, validating and making individual textural descriptions. The results showed that the strategy of strengthening the capacity of farmer groups through the manufacture of organic fertilizers in Tammerodo Sendana District, Majene Regency, namely: a) Human resource development strategy, b) Capacity development strategy in meeting needs, c) Providing facilities assistance, and d) Quality development fertilizer. Besides having the benefits of a strategy to strengthen the capacity of farmer groups in producing organic fertilizers such as human resource development, aspects of natural resources, social aspects, economic aspects.